Effects of Added Fat on Growth Performance, Carcass Characteristics, and Economics of Growing and Finishing Pigs Under Commercial Conditions - C. M. Vier; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; J. A. De Jong; C. Neill; E. Scholtz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 1,637 mixed gender pigs (PIC; 359 × Camborough) with an initial pen average body weight (BW) of 87.8 ± 2.39 lb were used in a 110-d growth trial to determine the effects of feeding increasing levels of dietary fat on performance of growing-finishing pigs from 88 to 286 lb. The trial was conducted from late June to early October. Pens of pigs were randomly assigned to 1 of 4 dietary treatments in a randomized complete block design with BW as a blocking factor. There were 16 replicate pens per treatment and 20 to 27 pigs per pen. The experimental diets were corn-soybean meal-based and were fed in 5 phases. The 4 dietary treatments were formulated to contain 0, 1.5, 3.0, and 4.5% added fat. During the grower and finisher periods, results of this study demonstrated no evidence of difference (P>0.05) in average daily gain (ADG) but a linear decrease (P<0.05) in average daily feed intake (ADFI) with increasing dietary fat level. During the grower period, there was a quadratic change (P<0.05) in feed-to-gain ratio (F/G). The greatest improvement in feed efficiency occurred as the dietary fat increased from 0 to 3%, with no improvements thereafter. During the finisher period, adding up to 4.5% fat to the diet resulted in a linear improvement (P<0.05) in F/G. Overall, there was no evidence of differences (P>0.05) in ADG and final BW as dietary fat level increased. Even though not statistically significant, changes in ADG were close to prior expectation and averaged 0.7% for every percent of added fat. Average daily feed intake decreased linearly (P<0.05) as the level of added dietary fat increased up to 4.5%. Increasing dietary fat level resulted in a quadratic improvement (P<0.05) in F/G. In addition, for every 1% fat increment, F/G improved on average 2.2%. For carcass characteristics, there was no evidence of differences (P>0.05) in hot carcass weight (HCW), percentage carcass yield, loin depth, and fat-free lean measurements due to increasing the level of added fat in the diet. Carcass backfat, however, increased linearly (P<0.05) with increased inclusion of fat in the diet from 0 to 4.5%. Feed cost per pig increased linearly (P<0.05) with increased dietary fat level. Feed cost per pound of gain increased quadratically (P<0.05) as the level of fat in the diet increased, with the highest cost per pound of gain observed at 4.5% fat inclusion. No evidence for differences (P>0.05) was observed for revenue per pig due to added fat in the diet. The increased feed cost in combination with lack of evidence of differences in revenue per pig resulted in a linear decrease (P<0.05) in income over feed cost (IOFC), with the highest income observed when pigs were fed diets with no added fat. The results of this experiment demonstrate that adding dietary fat mainly improved feed efficiency as expected. Also, economic decisions to use added fat depend on ingredient and pig market price, as well as potential of moving a larger proportion of lighter weight pigs into a higher value grid price.
Keywords: fat inclusion; finishing pigs; growth performance; economic analysis